HOW FINANCIAL RATIO AFFECTS FIRMS DIVIDEND PAYOUT POLICY IN SHARIA SECURITIES LIST? - Candy, Candy; Cahyani, Isty Rosy (2021)
This research aims to determine the effect of financial ratio on the dividend payout ratio of Efek Syariah companies in the Indonesian Stock Exchange (IDX). Financial ratio including current ratio, firm size, leverage, profitability, and free cash flow as the independent variables. The dependent variable uses the dividend payout ratio. This research uses company data between 2014 and 2018, consisting of 145 data samples of 30 companies. The sampling technique uses purposive sampling and analysis method tested by using panel regression. This result showed that firm size has a significant positive influence on the dividend payout ratio. Other variables like current ratio, leverage, profitability, and free cash flow do not significantly affect the dividend payout ratio.